Effects of triptolide on hippocampal microglial cells and astrocytes in the APP/PS1 double transgenic mouse model of Alzheimer′s disease - Jian-ming Li (Neural Regeneration Research, 2016)
The principal pathology of Alzheimer′s disease includes neuronal extracellular deposition of amyloid-beta peptides and formation of senile plaques, which in turn induce neuroinflammation in the brain. Triptolide, a natural extract from the vine-like herb Tripterygium wilfordii Hook F, has potent anti-inflammatory and immunosuppressive efficacy. Therefore, we determined if triptolide can inhibit activation and proliferation of microglial cells and astrocytes in the APP/PS1 double transgenic mouse model of Alzheimer′s disease. We used 1 or 5 μg/kg/d triptolide to treat APP/PS1 double transgenic mice (aged 4-4.5 months) for 45 days. Unbiased stereology analysis found that triptolide dose-dependently reduced the total number of microglial cells, and transformed microglial cells into the resting state. Further, triptolide (5 μg/kg/d) also reduced the total number of hippocampal astrocytes. Our in vivo test results indicate that triptolide suppresses activation and proliferation of microglial cells and astrocytes in the hippocampus of APP/PS1 double transgenic mice with Alzheimer′s disease.